Methylation Status of KLF4 Associated with Chronological Age - Nihad AM Al-Rashedi (Journal of Global Pharma Technology, 2016)
The expression of Krüppel-like factor 4 has associated with various biological processes including stem cell reprogramming and tumorigenesis. Although these advances in the epigenetic role of KLF4 expression in cancer and other physiological disorders, the methylation data of the KLF gene extracted from the previous studies that are not enough to coverage of non-coding of the KLF gene. In particular, the epigenetic mechanism is an essential regulator and the multiple studies reported DNA methylation level of many CPG sites in the human genome has a correlation with aging. This study highlights epigenetic changes of the KLF4 gene with aging. The present study included 92 blood samples from healthy persons, Arabic Iraqi population; age ranged 18-93 years, blood DNA samples subject to bisulfate DNA modification-pyrosequencing method. The statistical analysis detected a correlation between each CpG sites of the KLF4 gene, and age adopted the linear regression model using correction coefficient R2.Methylated 10 CpG sites of the KLF4 gene showed weakly correlated with age. R-values ranged from 0.1 to 0.2 and the highest value appeared in the CpG site 7 (Chr9: 107489111) R was 3.0. The fitting process using the simple regression model provided weak correction coefficients (R2 <80%) of the methylation levels of steady during the lifetime. The variance analysis suggested that there was no significant difference between the methylation levels of 10 CpG sites of intron 1 KLF4 gene and gender (P-values >0.05).Keywords: KLF4 gene, DNA methylation, Age, Pyrosequencing.